Design and Construction of a Machine for Squeezing Avocado Seeds into Oil as a Raw Material for Biodiesel Using a Screw Press - Munawar Reza; Muqadis Ilhafa; Taufan Arif Adlie; Zainal Arif; Teuku Azuar Rizal (Fakultas Teknik Universitas Samudra, 2024)
The manufacturing industry is growing rapidly, especially in terms of industrial workshops. According to BPS data for 2017, in 2016 the development of the manufacturing industry increased by 4.74%. Engineering design or machine design is a series of processes that translate the results of a system into performance, to explain work in detail on the components used. Mechanical pressing is the process of extracting fat or oil through pressure applied to grains with an oil content of around (30%-70%). The aim of the research is to design a machine for squeezing avocado seeds into oil using a screw press, to obtain the length of time for pressing avocado seeds using a screw press and the percentage of biodiesel raw material oil obtained from avocado seeds in 1 kg after going through degumming. This research was carried out using the machine design method, calculating the length of pressing time and the amount of avocado seed seepage. The load pressure on the press is 360 N/m with an electric motor capacity of 0.88 HP and a rotation speed of 17.5 ????????m. Pressing 1 kg of avocado seeds is 58:39 seconds then the raw material for biodiesel oil is 23 grams/1 kg.